PENGEMBANGAN MEDIA POSTER DIGITAL INTERAKTIF UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PADA MATERI SISTEM PENCERNAAN DI SEKOLAH DASAR - Carolita Natasha; Suratmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was motivated by the low level of students’ critical thinking skills in understanding the digestive system material in elementary school. The objective of this study was to develop an instructional medium in the form of an interactive digital poster to enhance the critical thinking skills of fifth-grade students at SD Negeri 25 Indralaya. This study employed the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects were fifth-grade students at SD Negeri 25 Indralaya. Data were collected through interviews, questionnaires, tests, observations, and documentation. The validation results indicated that the developed media was highly feasible, with a material expert validation score of 92.85%, media expert validation score of 94.23%, and practitioner expert validation score of 92.04%, all categorized as very feasible. The practicality test showed a very positive student response, with a score of 93.75% in the individual trial and 94.04% in the small group trial, both categorized as very practical. The effectiveness analysis based on the N-Gain score revealed a result of 0.979, which is classified as very high. Based on these findings, it can be concluded that the interactive digital poster developed in this study is highly feasible, practical, and effective in improving students’ critical thinking skills in the topic of the digestive system.